The Effectiveness of the Application of Electronic Ticketing Criminal Sanctions Against Traffic Violators in the Denpasar - Maharani, Luh Arini Yulia; Wulandari, Ni Gusti Agung Ayu Mas Tri (Dinasti Research, 2025)
The Bali traffic police implemented the Electronic Ticket System as an effort in law enforcement in terms of traffic violations. Electronic ticketing is an effort by traffic police officers to impose sanctions on traffic violators based on information technology. Denpasar City is used as an example in the implementation of the Electronic Ticket System by the Bali Police Traffic Directorate. However, in its implementation, there is a gap between the Bali Police Traffic Directorate and the people of Denpasar City regarding the wrong delivery address for electronic ticket confirmation letters that do not match the data of traffic violators that have been validated by traffic police officers in charge of the Back Office System. This research is an empirical legal research using a statutory approach and a factual approach. This research uses the basis of Lawrance M. Friedman's Legal System Theory. Data collection techniques are by conducting interviews and documentation studies. This research was conducted at the Bali Regional Police Traffic Directorate Unit. The mechanism for implementing this electronic ticketing system is to automatically snap traffic violators and then the results of the traffic violator snapshots are adjusted to the vehicle ownership data based on the vehicle number used when violating traffic. If it is valid, an electronic ticket confirmation letter will be issued which will be sent directly to the address of the traffic violator by the Bali Police traffic police